Assessing the deprivation gap in stillbirths and neonatal deaths by cause of death: a national population-based study. Issue 6 (6th March 2019) - Best, Kate E; Seaton, Sarah E; Draper, Elizabeth S; Field, David J; Kurinczuk, Jennifer J; Manktelow, Bradley N; Smith, Lucy K
Abstract : Objective: To investigate socioeconomic inequalities in cause-specific stillbirth and neonatal mortality to identify key areas of focus for future intervention strategies to achieve government ambitions to reduce mortality rates. Design: Retrospective cohort study. Setting: England, Wales, Scotland and the UK Crown Dependencies. Participants: All singleton births between 1 January 2014 and 31 December 2015 at ≥24 weeks' gestation. Main outcome measure: Cause-specific stillbirth or neonatal death (0–27 days after birth) per 10 000 births by deprivation quintile. Results: Data on 5694 stillbirths (38.1 per 10 000 total births) and 2368 neonatal deaths (15.9 per 10 000 live births) were obtained from Mothers and Babies: Reducing Risk through Audits and Confidential Enquiries across the UK (MBRRACE-UK). Women from the most deprived areas were 1.68 (95% CI 1.56 to 1.81) times more likely to experience a stillbirth and 1.67 (95% CI 1.48 to 1.87) times more likely to experience a neonatal death than those from the least deprived areas, equating to an excess of 690 stillbirths and 231 neonatal deaths per year associated with deprivation. Small for gestational age (SGA) unexplained antepartum stillbirth was the greatest contributor to excess stillbirths accounting for 33% of the deprivation gap in stillbirths. Congenital anomalies accounted for the majority (59%) of the deprivation gap in neonatal deaths, followed by preterm birth not SGA (24–27 weeks, 27%). Conclusions: Cause-specific mortality rates at a national level allow identification of key areas of focus for future intervention strategies to reduce mortality. Despite a reduction in the deprivation gap for stillbirths and neonatal deaths, public health interventions should primarily focus on socioeconomic determinants of SGA stillbirth and congenital anomalies.